Authors (The Biblical archaeology review, 2025)
Jeffrey P. Arroyo García (Nails or Knots—How Was Jesus Crucified?) is Associate Professor of Biblical Studies at Gordon College. He specializes in the Gospels and Greco-Roman Jewish literature. Jennie Ebeling (New Directions: How Archaeology Illuminates the Bible) is Associate Professor of Archaeology at the University of Evansville. Her research focuses on ancient food technologies and […]